Designing an IoT agriculture monitoring system for improving farmer’s acceptance of using IoT technology - Anas, Siti Aisyah; Sarban Singh, Ranjit Singh; Kamarudin, Nur Adilah (Engineering, Technology and Applied Science Research, 2021)
This paper describes Agri-Snaps, an Internet of Things (IoT) agriculture monitoring system designed to improve farmers’ acceptance of using IoT technology in their farm field. Agri-Snaps consists of four dedicated sensor circuit modules that integrate magnetic pogo pin connectors for easier assembly with the controller circuit module. This work investigated how such a design can enable the farmers to understand how 1) to assemble, 2) self-troubleshoot, and 3) maintain the monitoring system independently without requiring expertise on the farm site. User experience testing was conducted with ten participants to validate Agri-Snaps’s viability. The results showed that those participants positively rated Agri-Snaps as attractive, easy to understand and assemble, exciting, and innovative compared to the typical agriculture monitoring systems.